2011
DOI: 10.3233/jad-2011-110458
|View full text |Cite
|
Sign up to set email alerts
|

Review and Meta-Analysis of Biomarkers and Diagnostic Imaging in Alzheimer's Disease

Abstract: Mild Alzheimer's disease (AD) is often difficult to differentiate from mild cognitive impairment (MCI) or non-AD dementias. A multitude of diagnostic biomarkers and advanced imaging strategies have been developed to aid in the diagnosis and management of AD. We sought to review and analyze the published evidence on key test characteristics of major diagnostic strategies to formulate best estimates of sensitivity (SN) and specificity (SP). A systematic review was undertaken to locate and abstract all studies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
166
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(179 citation statements)
references
References 61 publications
7
166
0
6
Order By: Relevance
“…That same year, Silverman et al also published a compelling individual case presentation (27) demonstrating the important benefit obtained with PET metabolic imaging, as shown by its ability to detect AD in a patient who had been given multiple prior incorrect diagnoses of other neuropsychiatric disorders over the course of several years. During the past decade, many studies and literature reviews (28)(29)(30)(31) have demonstrated both the utility and the validity of PET metabolic imaging for evaluating dementia and related neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 99%
“…That same year, Silverman et al also published a compelling individual case presentation (27) demonstrating the important benefit obtained with PET metabolic imaging, as shown by its ability to detect AD in a patient who had been given multiple prior incorrect diagnoses of other neuropsychiatric disorders over the course of several years. During the past decade, many studies and literature reviews (28)(29)(30)(31) have demonstrated both the utility and the validity of PET metabolic imaging for evaluating dementia and related neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 99%
“…This result is encouraging for the development of validated universal biomarker cutoffs. Also, we would like to emphasize that our results should not delay the implementation of CSF biomarkers for evaluation of patients with AD symptoms in clinical practice at individual centers, because the clinical value of these biomarkers has been established in multiple, independent studies [25]. Rather, the variability stresses (i) the need for all laboratories to strive for longitudinal stability and to use validated internal cutoff levels, and (ii) the need for vendors to deliver more robust assays.…”
Section: Discussionmentioning
confidence: 99%
“…LCD ile AH'nın ayırıcı tanısında beyin FDG PET görüntüleme bulgularından yararlanılabilir (56,59,60,61,62). LCD'da AH'nda gözlenen temporoparietal hipometabolizmaya ek olarak oksipital de hipometabolizma bulgusu olması (56,59,62) ve posterior singulat korteks metabolizmasının kuneus ile prekuneus metabolizmasına göre daha çok korunmuş olmasından kaynaklanan "singulat adası bulgusu" LCD'nin AH'sinden ayırt edilmesini sağlayan özelliklerdir (62).…”
Section: Beyin Fluorodeoksiglukoz Pozitron Emisyon Tomografisibulgularıunclassified